INFLUENCE OF MANAGERIAL PERFORMANCE AGAINST PARTICIPATION BUDGET WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE - Baihaqi Ammy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research aims to prove whether there is influence between participation and managerial performance budgets to prove whether there is influence between the participation budget with managerial performance with organizational commitment as PDAM Tirtanadi moderating variables on the terrain. This type of research is a causal association. The technique of determination of the sample used is the census. The data used was obtained through questionnaires to the deployment of 32 employees who were on the level of management. This data will be analyzed using Multivariate Data analysis methods, where this method is a method of descriptive statistics and inferential that are used to analyze the data more than two variables of the study. Testing the quality of the data used is the validity of the data and test reliability. A classic assumption test used is the test of normality, multicollinearity test, and test heteroskedasticity. Hypothesis testing is a test – testing – t, F. This research resulted in the discovery of the three as has been proposed in the research hypothesis. First, the participation of influential managerial performance against budget. Second, the participation of the budget jointly with organizational commitment effect significantly to managerial performance. Third, the variable of organizational commitment is not moderating variable.